2022
DOI: 10.1021/acs.jafc.2c00641
|View full text |Cite
|
Sign up to set email alerts
|

Pterostilbene and Its Derivative 3′-Hydroxypterostilbene Ameliorated Nonalcoholic Fatty Liver Disease Through Synergistic Modulation of the Gut Microbiota and SIRT1/AMPK Signaling Pathway

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a recent chronic liver disease common in many developed countries and is closely associated with metabolic syndrome, such as obesity and insulin resistance. The present study was performed to investigate the effects of pterostilbene (Pt) and its derivative 3′-hydroxypterostilbene (OHPt) on free fatty acids (FFA)-induced lipid accumulation in HepG2 cells and high-fat diet (HFD)-induced NAFLD in C57BL/6J mice. The results showed that Pt and OHPt significantly ameliorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…We also found that GDK decreased the abundance of Phascolarctobacterium , Clostridium_IV, and Megamonas flora. Phascolarctobacterium is related to the production of short-chain fatty acids such as acetate and propionate and has a certain detoxification effect [ 58 ]. The role of Clostridium_IV and Megamonas in liver diseases has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that GDK decreased the abundance of Phascolarctobacterium , Clostridium_IV, and Megamonas flora. Phascolarctobacterium is related to the production of short-chain fatty acids such as acetate and propionate and has a certain detoxification effect [ 58 ]. The role of Clostridium_IV and Megamonas in liver diseases has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The cells were exposed to indicated concentrations of 5-ATAN for various time periods at 37 °C. Then, they were washed with cold PBS and harvested, and a Western blot was conducted as previously described [ 46 , 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, PTS and its derivative 3′-Hydroxy-pterostilbene reduced NAFLD pathogenesis induced by free fatty acids and a fat-rich diet through the upregulation of SIRT1/AMPK and insulin signaling pathways and the downregulation of the protein expression of SREBP-1, which results in the activation of the β-oxidation of fatty acids and the consequent reduction in fatty acid synthesis. Moreover, PTS was also observed to promote the growth of vital beneficial microbiota, such as Oscillospira, while down-regulating the population of potentially pathogenic bacteria, such as Allobaculum, Phascolarctobacterium, and Staphylococcus [ 104 ].…”
Section: Therapeutic Properties Of Ptsmentioning
confidence: 99%